Detection of Bombyx mori as a Protein Source in Feedingstuffs by Real-Time PCR with a Single-Copy Gene Target - Aline Marien; Benjamin Dubois; Abigaël Anselmo; Pascal Veys; Gilbert Berben; Cloé Kohl; Julien Maljean; Stéphanie Guillet; Jean-François Morin; Frédéric Debode (Agriculture)
The silkworm, Bombyx mori, is reared on a large scale, mainly for silk production. The waste from this silk production, like pupae, is underused. As an edible insect, B. mori is a good source of protein in human food and animal feed. In recent years, European legislation on the use of insects has evolved and a multitude of European companies have initiated the rearing of insects specifically for food and feed applications. Regarding animal feed, Commission Regulations (EU) 2021/1372 and 2021/1925 authorize eight insect species, including silkworm, as processed animal proteins for use in fish, pig, and poultry feed. The incorporation of edible insects into the human diet falls within Regulation (EU) No. 2015/2283 concerning novel foods. Implementation of authentication methods is imperative to ensure the conformity of the products. In the present study, we propose a specific real-time PCR method for the detection of silkworm (B. mori). The developed PCR test amplifies a 98 bp fragment of the cadherin gene. This gene is present in a single-copy per haploid genome, as demonstrated by experimental evidence. The qualitative method was successfully evaluated on the performance criteria of specificity, sensitivity, efficiency, robustness, and transferability. The applicability of the test was assessed on samples of B. mori from industry. Light microscopy and DNA metabarcoding approaches were used as a complement to genomic analysis as a means of providing authentication of the samples.